Barriers and facilitators to vaccination in Latin America: a thematic synthesis of qualitative studies - Javier Roberti; Natalí Ini; Maria Belizan; Juan Pedro Alonso (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Vaccines are often undervalued or underused for a variety of reasons, and vaccine hesitancy is a global challenge that threatens vaccine acceptance and the goals of immunization programs. This review aimed to describe the barriers and facilitators to vaccination in Latin America. The study design was a systematic review and thematic synthesis of qualitative studies reporting on the knowledge or attitudes of adults, parents of children at vaccination age, adolescents and health professionals towards vaccination in Latin America. The databases searched were PubMed, CENTRAL, Scopus, LILACS, SciELO, and CINAHL. A total of 56 studies were included. Facilitators included vaccination being recognized as an effective strategy for preventing infectious diseases and as a requirement for access to social assistance programs, schooling or employment. Recommendations from health professionals and positive experiences with health services were also identified as facilitators. The main barriers were lack of information or counseling, structural problems such as shortages of vaccines and limited hours of operation, the inability to afford over-the-counter vaccines or transportation to health facilities, certain religious beliefs, misconceptions and safety concerns. Qualitative research can contribute to understanding perceptions and decision-making about vaccination and to designing policies and interventions to increase coverage.